Pelayanan Publik Berbasis Online Pada Dinas Komunikasi dan Informatika Kota Tangerang - Mulianingsih, Intan; Asmawi, M Rosul; Firdiyani, Fitria (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research focuses on problems where in the era of digitalization where technology is growing more rapidly. Therefore, the community demands acceleration in terms of public services. So that people can carry out public services easily online without having to come directly to the relevant office. As well as the process carried out can be more effective and does not require a long time. For this reason, the purpose of this research is to find out the implementation of online-based public services at the tangerang city communication and information service. And to find out the obstacles faced by the tangerang city communication and information service in providing online-based public services. This study uses descriptive qualitative methods and analyzes the theory of electronic services (service quality) from zeitahml and parasuraman. The results of research on online-based public services at the tangerang city communication and informatics office are good because the tangerang city communication and informatics office has utilized and optimized information technology to provide public services by developing online-based services that can be easily accessed from anywhere and at any time. However, there are obstacles that come from the community, namely online-based public services that have not been utilized by the whole community. And constraints on several websites and also application features that cannot be accessed so that it can become an obstacle in providing public services online.